Assessment of Sport Performance: Theoretical Aspects and Practical Indications - Tiziana D'Isanto; Francesca D'Elia; Gaetano Raiola; Gaetano Altavilla (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Sport evaluation is a fundamental moment in the training process of every athlete, every team and is an indispensable support for the coach. The aims and all the aspects related to the assessment, will be taken into consideration, together to that can have a positive effect on performance, allowing each athlete, team and coach a good workout or match, whatever their competitive level. The approach is argumentative theoretical for the part relating at the training theory. Firstly, summarizing and deducting the scientific idea of research and of apply it in the practices of measurement and evaluation of the sport performance. One of the topics investigated is the relationship between genetic factors and training factors, in determining the performance of an athlete. The athlete's evaluation process should be useful in setting up and controlling the training and providing information to improve sport performance.